Mulheres, Gênero e Sexualidades na sociedade diversos olhares sobre a cultura da desigualdade - Brabo, Tânia Suely Antonelli Marcelino (Editora Oficina Universitária, 2020)
This collection is the result of Tânia Suely Antonelli Marcelino Brabo's tireless commitment to the systematization and dissemination of the gender debate in Human Sciences in its most varied areas. This volume articulates the themes of gender and human rights, contributing to the reflection on topics still considered controversial today and, currently, under the crosshairs of the anti-gender attack. With different perspectives, the texts compiled here help us to recover a long path in which the different dimensions of the expansion of human rights from the perspective of gender relations face the production of inequalities imposed on women and LGBTQIA+ people in their multiple forms of oppression. But it goes further by also registering the resistance and construction of an expanded citizenship capable of collective achievements created and strengthened in joint action. In times of extreme challenges imposed by the pandemic caused by the new coronavirus, with the intensification of death and the subalternization of women and people who are part of the LGBTQIA+ community, we invite you to read a work of important contribution in considering gender social relations as a dimension that structures social inequalities and drives the fight for rights.